First, put the equation in standard quadratic form:
(x - 3)^2 = 5
(x - 3)(x - 3) = 5
x^2 - 3x - 3x + 9 = 5
x^2 - 6x + 9 = 5
x^2 - 6x + 9 - color(red)(5) = 5 - color(red)(5)
x^2 - 6x + 4 = 0
We can now use the quadratic equation to solve this problem:
The quadratic formula states:
For color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0, the values of x which are the solutions to the equation are given by:
x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))
Substituting:
color(red)(1) for color(red)(a)
color(blue)(-6) for color(blue)(b)
color(green)(4) for color(green)(c) gives:
x = (-color(blue)(-6) +- sqrt(color(blue)(-6)^2 - (4 * color(red)(1) * color(green)(4))))/(2 * color(red)(1))
x = (6 +- sqrt(36 - 16))/2
x = (6 +- sqrt(20))/2
x = (6 - sqrt(4 * 5))/2; x = (6 + sqrt(4 * 5))/2
x = (6 - sqrt(4)sqrt(5))/2; x = (6 + sqrt(4)sqrt(5))/2
x = (6 - 2sqrt(5))/2; x = (6 + 2sqrt(5))/2
x = 6/2 - (2sqrt(5))/2; x = 6/2 + (2sqrt(5))/2
x = 3 - sqrt(5); x = 3 + sqrt(5)